The Role of E-learning on Enhancing the Achievement from the Point of View of Secondary Schools’ Principal During the Corona Pandemic - Shdeifat, Lana Muhammed (Journal of Curriculum and Teaching Methodology, 2022)
This study aimed to reveal the role of e-learning on enhancing the achievement of students from the point of view of the principals of secondary schools During the Corona Pandemic. To achieve the goals of the study descriptive analytical approach was used. The study sample consisted of (54) school principal from the principals of public secondary schools in Zarqa Governorate. Data were collected through a questionnaire which consisted of (20) items. The results revealed that the study sample’s evaluation of the role of e-learning on enhancing students’ achievement was low with mean of (2.62), and the results also revealed that there are no statistically significant differences in the means of the study sample’s evaluations of the role of e-learning on enhancing students’ academic achievement according to the gender variable, and the researcher recommended conducting training courses in the field of e-learning for both teachers and students.
Keywords: E-Learning; The Achievement; Secondary Schools; Principal